2022
DOI: 10.1146/annurev-marine-032521-103517
|View full text |Cite
|
Sign up to set email alerts
|

The Functional and Ecological Significance of Deep Diving by Large Marine Predators

Abstract: Many large marine predators make excursions from surface waters to the deep ocean below 200 m. Moreover, the ability to access meso- and bathypelagic habitats has evolved independently across marine mammals, reptiles, birds, teleost fishes, and elasmobranchs. Theoretical and empirical evidence suggests a number of plausible functional hypotheses for deep-diving behavior. Developing ways to test among these hypotheses will, however, require new ways to quantify animal behavior and biophysical oceanographic proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 142 publications
1
50
0
Order By: Relevance
“…However, many of these species frequented deeper bathomes, with 31 recorded at mesopelagic depths (>200 m) and 13 at bathypelagic depths (>1000 m). The motivation for irregular movements into deep, dark, cold waters for epipelagic species is difficult to determine but could be related to some combination of foraging opportunities, thermoregulation, bioenergetics, reproduction, predator avoidance, and/or navigation through magnetic, chemical, topographic, electric, and light cues ( 20 ). Entering deep waters for sustained periods, however, requires a capacity to endure cooler temperatures and potentially more hypoxic conditions that are likely to be outside the “normal” environmental niche of many epipelagic species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many of these species frequented deeper bathomes, with 31 recorded at mesopelagic depths (>200 m) and 13 at bathypelagic depths (>1000 m). The motivation for irregular movements into deep, dark, cold waters for epipelagic species is difficult to determine but could be related to some combination of foraging opportunities, thermoregulation, bioenergetics, reproduction, predator avoidance, and/or navigation through magnetic, chemical, topographic, electric, and light cues ( 20 ). Entering deep waters for sustained periods, however, requires a capacity to endure cooler temperatures and potentially more hypoxic conditions that are likely to be outside the “normal” environmental niche of many epipelagic species.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies on elasmobranch depth distributions have generally been conducted on a species-specific basis ( 14 , 16 , 17 ). Yet, an early study ( 18 ) and recent reviews have identified consistent vertical patterns among certain taxa, including diel vertical movement (DVM) and deep-diving behaviors ( 19 , 20 ). Furthermore, a recent synthesis of a regional predator assemblage in the South Atlantic revealed that dynamic species-specific space use was tied to water column structure ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion does not negate other reasons for extensive forays into the water column. For example, oscillatory and or 'yo yo' deep-diving and surfacing events can serve several functions (reviewed by Braun et al 2022) Vol:. ( 1234567890) chemical cues, improving magnetic perception and thermoregulation (Nelson et al 1997;Klimley et al 2002;.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the maximum size reached by migratory predators (L Mig cut = 1.5m) is below the maximum size allowed by the model (2 m), while observations show the occurrence of larger species (max(Lm Mig obs ) > 2 m), such as swordfish or white sharks. Many large deep-diving predators develop thermoregulation apparatuses (Legendre and Davesne, 2020;Braun et al, 2021) that might increase feeding efficiency and assimilation in deep waters (Fritsches et al, 2005). These adaptations may contribute to the increased asymptotic size of migratory species, but are absent in the model.…”
Section: Emergent Featuresmentioning
confidence: 99%
“…Moreover, in the model, large pelagic predators completing diel migrations spend half of the day at depth, half of the day at the surface. This pattern is applied to all migratory predators; however, some species adopt different behaviors, e.g., sub-daily vertical migrations with sporadic deep dives (Braun et al, 2021). Fine-tuning or new parameterizations could also help reduce this bias (see Figure 6).…”
Section: Emergent Featuresmentioning
confidence: 99%